2013
DOI: 10.1016/j.ijscr.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic nerve compression by an extrapelvic cyst secondary to wear debris after a cementless total hip arthroplasty: A case report and literature review

Abstract: This case shows us that sciatic neuropathy with no evidence of nerve root impingement on lumbar MRI in a patient with THA requires also examination of the hip and pelvis with detailed radiological methods, such as MRI, in addition to plain radiography. Removal of the source of debris via revision surgery following subtotal cystectomy leads to the resolution of the remaining portion of the cyst and also relief of the symptoms of sciatic nerve compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…These particles cause inflammation initially, which increases the number of inflammatory cells, and especially the numbers of macrophages and fibroblasts, in the joint fluid. The intraarticular pressure also rises, and the wear particles from the joint’s surfaces can migrate from the area, even when the prosthesis is very tight, and they will eventually spread throughout the joint cavity [ 22 - 24 ].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…These particles cause inflammation initially, which increases the number of inflammatory cells, and especially the numbers of macrophages and fibroblasts, in the joint fluid. The intraarticular pressure also rises, and the wear particles from the joint’s surfaces can migrate from the area, even when the prosthesis is very tight, and they will eventually spread throughout the joint cavity [ 22 - 24 ].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Osteolysis surrounding prosthesis has been defined as a complication that is caused by wear debris, and affects the clinical outcome of THA [1]. There are many reports of osteolysis and accompanying enlargement of the cyst [2][3][4][5][6][7], but few reports present pathological findings [2,3]. The pathological findings of our case indicated that there were polyethylene particle-like substances in abundant macrophages, and hemosiderin was present in the interstitium of the tissue.…”
Section: Discussionmentioning
confidence: 58%
“…Thus, the findings of this case (presence of polyethylene particles and hemosiderin) do not contradict the causative factors in the rapidly progressive periprosthetic osteolysis and cystic lesion. It is important that we make an early diagnosis of progressive osteolysis after THA, because there may be severe complications in cases where hematoma and hemosiderin deposits coexist in osteolysis, such as cystic tumor increase, urinary obstruction disorder, femoral nerve paralysis, sciatic nerve paralysis and abdominal organ pressure [2,3,5,7]. It is often difficult to predict the progression of osteolysis because most cases are asymptomatic [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, opinion differs over the optimal treatment for periprosthetic cysts, with the options including cystectomy, cyst paracentesis, and cystectomy with revision of prosthesis. Among our six patients, three were treated in other departments first, and because they did not follow standardized recommendations for the treatment of periprosthetic cysts, the treatments in these cases were not the same.…”
Section: Discussionmentioning
confidence: 97%